Impact of El Niño on the Productivity and Income of Conventional and Organic Oil Palm Farmers at Penawar Tama, Tulang Bawang Regency - Siti Ghalika Permata Suri Almega; Zainal Abidin; Yaktiworo Indriani; Ktut Murniati; Fembriarti Erry Prasmatiwi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Extreme weather condition such as El Niño phenomenon potentially result in great effect on farm production. This study aims to analyze the effect of El Niño on the productivity and income of organic and conventional oil palm farming. The research was conducted in Penawar Tama Subdistrict, Tulang Bawang Regency, during March–April 2024, using a survey involving 56 oil palm farmers. Data were analyzed using paired sample t-test, Wilcoxon Signed Rank, Mann-Whitney test, and described qualitatively. Results indicate that El Niño phenomenon had significant negative impacts on productivity, revenue, and farmer income, as evidenced by the premature fruit drop under extreme drought conditions. Specifically, oil palm productivity declined by 19.14% for organic farm, and by 20.46% for conventional farm. The income of organic oil palm farmers fell by 61.70% (equivalent to 7,400,446.44 IDR/ha), and that of conventional farmers declined by 127.09% (equivalent to 5,048,508.01 IDR/ha). The paired sample t-test and Wilcoxon Signed Rank test revealed significant differences in productivity, total costs, Fresh Fruit Bunch (FFB) prices, revenue, and income before and during El Niño phenomenon, with significance values of less than 0.05. The Mann-Whitney test showed significant differences in productivity, total costs, revenue, and income between organic and conventional oil palm farming during the El Niño. However, no significant difference was found in FFB selling prices.